Adaptive area-wide management for suppressing spruce budworm outbreaks: effectiveness of the early intervention strategy - Rob C. Johns; S. Edwards; L. Amos-Binks; J. J. Bowden; D. Carleton; C. Edge; C. Hennigar; P. James; D. MacLean; V. Martel; E. R. D. Moise; B. Morin; et al. (Journal of Pest Science, 2026)
In eastern North America, two main insecticide-based strategies are used to manage spruce budworm ( Choristoneura fumiferana ) outbreaks. The traditional ‘Foliage Protection Strategy’ (FPS) focuses on temporarily reducing defoliation and tree mortality in high-value stands, allowing outbreaks to progress naturally in surrounding areas. The ‘Early Intervention Strategy’ (EIS) is an adaptive, area-wide management approach that targets low-density “hotspots” to prevent outbreak growth and spread. We report findings from a 10-year case study (2015–2024) in Atlantic Canada assessing EIS effectiveness. EIS treatments consistently reduced population growth rates, resulting in a 12–67% reduction in hotspot areas compared to untreated areas. Crucially, this suppression curbed the rise and spread of the outbreak across northern New Brunswick, with negligible defoliation observed throughout the study period. By comparison, in a neighboring Quebec study area contemporaneously managed with FPS, the outbreak advanced normally, causing moderate to severe defoliation over ~ 1.7 million hectares by 2024. Moreover, EIS required ~ 80% less insecticide, with 66% of treated areas receiving treatment in only a single year, compared with just 15% under FPS. Our findings provide robust evidence for the effectiveness of EIS when implemented under suitable conditions, highlighting its potential as a proactive outbreak management approach.

Precision of age assignment from four structures of smallmouth buffalo [Ictiobus bubalus, (Rafinesque, 1818)] in the Southeastern United States - Jason C. Doll; Autumn Morin; Jason Marsik; Gatlin Edge; Gavin McAbee; Luke Etchison (Environmental Biology of Fishes, 2026)
Accurate and precise age determination is essential for estimating key life-history parameters in fishes. Recent studies suggest that some fisheries management metrics, such as mortality, may be robust to biased age estimates. Thus, it can be more important to identify the most precise structure for age assignment. However, precision can vary geographically, highlighting the need for location-specific evaluations. Smallmouth buffalo [ Ictiobus bubalus , (Rafinesque, 1818)] have received little attention in this regard, particularly outside their native range. We compared the precision of four structures, scales, opercles, otoliths, and anal fin rays, for assigning ages to smallmouth buffalo from a large river in the Southeastern United States. Anal fin rays showed the highest between-reader agreement, with the lowest coefficient of variation (CV) and average percent error (APE), followed by otoliths, opercles, and scales. Ages assigned from scales, opercles, and anal rays were generally consistent with otolith ages up to age 12. Variability in age assignments had little effect on von Bertalanffy growth parameters or mortality estimates between otoliths and anal rays, and these models were generally consistent across readers. Overall, our results indicate that anal fin rays provided the most precise age estimates for smallmouth buffalo in this system. Although bias was not assessed, the close agreement between anal fin ray and otolith ages suggests that anal fin rays are a reliable, non-lethal option for aging individuals less than 12 years old.

Historical pesticide applications for the treatment of eastern spruce budworm infestations in New Brunswick - Shane Heartz; David A. MacLean; Rob C. Johns; Drew Carleton; Luke Amos‐Binks; Quinn Anderson; Yue Yu; Andrew D. Lewis; Dan Lavigne; Joseph B. Burant; Christopher B. Edge (Ecology, 2023)
Pesticides have been used in Canada since 1945 as part of large‐scale aerial spray applications to control insect pests on forested lands. Some of the pesticides used historically were efficacious, nonselective, persistent, and have led to serious impacts on the environment. A well known, and extensively documented example is the large‐scale aerial spray programs in New Brunswick, Canada. From 1952 to 1993, 97% of the 6.2 million ha of the forested lands of New Brunswick were treated with at least one application of one insecticide, the majority of which were applied to control outbreaks of eastern spruce budworm ( Choristoneura fumiferana ). The most well known insecticide was dichlorodiphenyltrichloroethane (DDT), applied from 1952 to 1968, which still persists in treated soils and adjacent water bodies, and caused the individual and cumulative ecosystem effects that can still be measured today. The insecticides that replaced DDT were nonpersistent and unlikely to be found today. However, during the years of application some of the insecticides were likely to have impacted local ecosystems to some degree. To aid future studies on the efficacy and environmental impact of these insecticides we created a digital spatial data set of known pesticide application in New Brunswick forestry from 1952 to 1993. The data set includes active ingredient, formulation, application rate, tank mix, aircraft type, and other ancillary information. The current version of the data is available on the New Brunswick Department of Natural Resources and Energy Development, GIS Open Data Page and in the supplemental material. Use of the data set for academic and educational purposes is encouraged, provided that both this data paper and the data source are properly cited; the Government of New Brunswick should be acknowledged as the data source (Open Government License http://www.snb.ca/e/2000/data-E.html ).

Community vulnerability to the health effects of climate change among indigenous populations in the Peruvian Amazon: a case study from Panaillo and Nuevo Progreso - I. Hofmeijer; J. D. Ford; L. Berrang-Ford; C. Zavaleta; C. Carcamo; E. Llanos; C. Carhuaz; V. Edge; S. Lwasa; D. Namanya (Mitigation and Adaptation Strategies for Global Change, 2013)

Indicators of environmental stress: cellular biomarkers and reproductive responses in the Sydney rock oyster (Saccostrea glomerata) - Katelyn J. Edge; Emma L. Johnston; Anthony C. Roach; Amy H. Ringwood (Ecotoxicology, 2012)

Octopamine and serotonin have opposite effects on antipredator behavior in the orb-weaving spider, Larinioides cornutus - Thomas C. Jones; Tamer S. Akoury; Christopher K. Hauser; Michael F. Neblett; Brent J. Linville; Andrea A. Edge; Nathaniel O. Weber (Journal of Comparative Physiology A, 2011)

Effects of Commercial Microbial Products on the Immune System of Elliptio complanata Mussels - F. Gagne; T. Edge; M. Douville; C. Blaise (Bulletin of Environmental Contamination and Toxicology, 2006)